Determinatio of Psychometrics Index of SNAP-IV Rating Scale in Parents Execution - Seyyed Jalal Sadrosadat; Zahra Houshyari; Reza Zamani; Leila Sadrosadat (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: SNAP-IV rating scale to diagnosis Attention Deficit Hyperactivity Disorder (ADHD) developed by Swanson, Nolan and Pelham. The aim of this study is determination of psychometrics specifications of this scale. Materials & Methods: This Descriptive research is a methodological, applied and validity assessment study. One thousand students at 7 to 12 age of primary school in Tehran city were selected by cluster sampling. Then the students mothers was asked to complete rating scale to consider behavior of their children.30 staff members of sample group were retest after one mounts. Diagnostic interview was administered at 36 members of sample group. Data were analyzed by using pearsonian correlation coefficient, Kolmogorof - Smirnoff and Behrens - Fisher T test. Results: Criterion validity was 48%, factor analysis was detected 3 factors that explain 56% of the total variance. Reliability coefficient was 82% . internal consistency coefficient was 90% and split -half coefficient was 76%, Cut-off point in scale and subscales was 1.57,1.47 and 1.9 respectively. Conclusion: The SNAP-IV Rating scales have fit psychometrics specifications. Therefore, it is useable in various diagnostic and therapeutic conditioning.